Differential methylation in blood pressure control genes is associated to essential hypertension in African Brazilian populations - Camila Cristina Avila Martins; Mariana Maschietto; Lilian Kimura; Lucas Alvizi; Kelly Nunes; Vinícius Magalhães Borges; Ana Cristina Victorino Krepischi; Regina Célia Mingroni-Netto (Epigenetics)
While genetic studies have provided insights into essential hypertension (EH, defined by high blood pressure ≥140/90 mmHg), investigation through epigenetics may address gaps in understanding its heritability. This study focused on African Brazilian populations in Vale do Ribeira River region, due to their high hypertension prevalence. We aimed to determine if DNA methylation is linked to hypertension susceptibility, through a genome-wide evaluation of 80 peripheral blood samples from normotensive (39) and hypertensive (41) individuals, with Infinium Methylation EPIC BeadChip platform. Data were analyzed using ChAMP package and cross-referenced with information from databases such as EWAS Atlas, GWAS catalog, GeneCards, literature, and tools such as VarElect and EWAS Toolkit. The comparison between hypertensive and normotensive revealed 190 differentially methylated CpG positions (DMPs) and 46 differentially methylated regions (DMRs), both with p-value ≤0.05. Among the DMPs, 27 were found to have a plausible role in blood pressure. Among the DMRs, those mapped to ABAT, BLCAP, CERS3, EIF4E, FMN1, GABBR1, HLA-DQB2, HOXA5, IL5RA, KCNH2, MIR487B, MIR539, MIR886, MKRN3, NUDT12, PON3, RNF39, RWDD3, and TSHBS1 were highlighted because of their lowest p-values, current literature, and/or VarElect prioritization. Our findings suggest that differences in methylation contribute to the high susceptibility to essential hypertension in these populations.